2019
DOI: 10.1097/01.asw.0000549611.06727.52
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Experience of Hidradenitis Suppurativa Management

Abstract: BACKGROUND: Although treatment recommendations for hidradenitis suppurativa (HS) are well known, practical experience implementing them in Lithuania has not been reported yet. OBJECTIVE: To review clinical findings and treatment options used in patients with HS in the largest center of dermatology and venereology in Lithuania from 2005 to 2016. METHODS: A retrospective single-center medical file analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Four studies reported data on excision and unroofing collectively in retrospective studies, representing 876 patients [ 25 , 35 , 36 , 59 ]. Two studies reported grouped recurrence rates across multiple procedures (e.g., excision, unroofing) and did not specify intervention [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported data on excision and unroofing collectively in retrospective studies, representing 876 patients [ 25 , 35 , 36 , 59 ]. Two studies reported grouped recurrence rates across multiple procedures (e.g., excision, unroofing) and did not specify intervention [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies specified postoperative complications, with an overall rate of 4% (81 complications/765 patients) [ 25 , 36 , 59 ]. The top complication was infection ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many epidemiological studies from different countries have been reported in the literature about HS. 7,[9][10][11][12] A limited number of epidemiological studies have been reported related to HS in Turkey. 13,14 Hurley described a clinical severity score for HS in 1989.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, granuloma formation; abscesses, histiocytes and sinuses surrounded by giant cells can be seen. 10 In the literature, many studies have mentioned the relationship between smoking and obesity with HS. Smoking is thought to play a role in etiology by increasing the chemotaxis of polymorphonuclear leukocytes.…”
Section: Severity Of Hsmentioning
confidence: 99%